Quality in VET in European SMEs : a review of the food processing, retail and tourism sectors in Germany, Ireland and Greece - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"Small enterprises are predominant in all European economies and are also important providers of jobs. However, despite the fact that SMEs are seen as an important source of dynamic development and innovation, they tend to carry out little training. The wide variety of training provision and the generally limited extent of training itself, make the issue of quality in small enterprise training more important. Hence, the questions that the present study is addressing of whether small enterprises have a quality approach to training and of how, and under what conditions, such approaches are or could be introduced and maintained. The study sets out to investigate small enterprises in specific sectors in which SME presence is particularly pronounced, in three Member States (Germany, Ireland and Greece) and to draw comparisons between them. Particular emphasis is placed on 'sector logic', the sectors' special characteristics and the national cultural and institutional environment." (Hrsg., BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; S 1.5.3 Betriebliche Weiterbildung; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; L 6 Qualität; G 1.2.4.1.4 Verarbeitendes Gewerbe; G 1.2.4.2.1 Handel, Instandhaltung, Reparatur von Kfz und Gebrauchsgütern; G 1.2.4.2.3 Gastgewerbe; I 2.1 Deutschland; I 2.2.1 Westeuropa; Personalentwicklung; Betriebliche Weiterbildung; On-the-job training; Klein- und Mittelbetrieb; Qualitätssicherung; Nahrungs- und Genussmittelgewerbe; Einzelhandel; Tourismus; Bundesrepublik Deutschland; Irland; Griechenland